PENGARUH MEDIA SOSIAL TERHADAP MINAT BELI KONSUMEN STUDI KASUS MAHASISWA MANAJEMEN UNIVERSITAS PASIR PENGARAIAN - Setiawati, Mila; 'Aini, Yulfita; Aida, Welven (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This research was conducted at the University Pasir pengaraian of Management Studies Program and than the research aims to determine the effect of social media on consumer buying interest Management student of the University Pasir Pengaraian. This research was conducted using quantitative data, data collection in this study using a questionnaire containing 20 grains of questions and distributed to 85 respondents who had made a purchase at any store online shop at least one time. The sampling technique that researchers do that is to use the formula slovin. Analysis of data used in this study is to test hypotheses using validity and reliability testing.Â The results of the regression analysis indicate there is a very strong and significant correlation between social media with consumers buying interest on Student Management Studies Program University of Pasir Pengaraian that is equal to 0.632, or by 63.2%. Researcher suggest that consumers shopping in social media can visit the the sites are trusted and should be more careful in use the services an online shop that was not disappointed to consumers.